Adaptation of Spike Timing Precision Controls the Sensitivity to Interaural Time Difference in the Avian Auditory Brainstem - Higgs, Matthew H. (Society for Neuroscience, 2012)
While adaptation is widely thought to facilitate neural coding, the form of adaptation should depend on how the signals are encoded. Monaural neurons early in the interaural time difference (ITD) pathway encode the phase of sound input using spike timing rather than firing rate. Such neurons in chicken nucleus magnocellularis (NM) adapt to ongoing stimuli by increasing firing rate and decreasing spike timing precision. We measured NM neuron responses while adapting them to simulated physiological input, and used these responses to construct inputs to binaural coincidence detector neurons in nucleus laminaris (NL). Adaptation of spike timing in NM reduced ITD sensitivity in NL, demonstrating the dominant role of timing in the short-term plasticity as well as the immediate response of this sound localization circuit.